Investigating the relationship between quality of life and hope in family caregivers of hemodialysis patients and related factors - Seyedeh Azam Sajadi (BMC, 2021)
Abstract Background Family caregivers of hemodialysis patients are the first and most crucial source of care at home. They experience many problems in the care of hemodialysis patients, which can affect their quality of life and hope, affecting the quality of care provided to patients. This study aimed to determine the relationship between quality of life and hope in family caregivers of hemodialysis patients. Methods A cross-sectional (descriptive-analytical) study performed on 300 family caregivers in the east of Mazandaran province in Iran. Data were collected using the Family Caregiver Quality of Life (FQOL), SF8 and adult hope scale. Data analysis was performed in SPSS version 16, and a P-value of below 0.05 was considered statistically significant. Results The results showed that, there was a direct and significant relationship between hope and quality of life. However, the quality of life was significantly lower in suburban residents, the unemployed, spouses, people with lower education and income levels, caregivers who cannot leave their patients alone, those living with their patients in the same house, and those taking care of male patients, compared to other participants (P < 0.05). Suburban residents, the unemployed, people with an insufficient level of income, and those living with their patients in the same house had significantly lower hope, compared to other subjects. Conclusion Since an increase of hope and quality of life of caregivers can cause improved quality of patient care, it is recommended that hope-based educational programs and interventions be implemented for caregivers.